PO138 High disease activity in relapsing multiple sclerosis (rms). (1st December 2017) - Giovannoni, Gavin; Rammohan, Kottil; Cook, Stuart; Comi, Giancarlo; Rieckmann, Peter; Soelberg-Sorensen, Per; Vermersch, Patrick; Dangond, Fernando; Hicking, Christine
Abstract : Background: The CLARITY study in patients with RMS allows assessment of high disease activity (HDA) definitions for identifying patients with higher rate of relapse or disability progression. Objective: Evaluate clinical/MRI criteria to identify HDA among placebo recipients in CLARITY. Methods: Placebo recipients in CLARITY (n=437) were analysed using criteria of high relapse activity ([HRA]≥2 relapses in the previous year) regardless of prior treatment, or a HRA plus treatment nonresponse ([HRA +TNR]≥2 relapses in the previous year OR ≥1 relapse in previous year on DMD therapy and ≥1 T1 Gd +or ≥9 T2 lesions). Identification of HDA was assessed by relapse and disability outcomes. Results: ARR was higher in the HRA (0.5, 95% CI 0.41–0.60) and HRA+TNR subgroups (0.47, 95% CI 0.40–0.57) than the overall placebo population (0.35, 95% CI 0.31–0.39), and non-HRA and non-HRA +TNR subgroups (0.29, 95% CI 0.24–0.34 each). Time to 6 month confirmed EDSS progression (10% of patients) was 110 days for the HRA subgroup (non-HRA=330 days), 162 days for the HRA+TNR subgroup (non-HRA +TNR =329 days) and 245 days (overall placebo). Conclusions: HDA criteria based on relapse history, treatment history and MRI characteristics can identify patients at increased risk of experiencing relapses and disability progression.